Advent of paradoxical flow after antihypertensive treatment in mid-ventricular obstructive hypertrophic cardiomyopathy – A case report. Issue 4 (April 2023) - Misumi, Ikuo; Wada, Kuniyasu; Sato, Koji; Tabira, Akihisa; Usuku, Hiroki; Tsujita, Kenichi
Abstract: A 69-year-old woman was admitted our hospital due to acute cerebral infarction. Transthoracic echocardiography showed massive left ventricular (LV) hypertrophy with small ventricles and normal LV ejection fraction. Apical 4-chamber and longitudinal images showed mild LV obstruction. After treatment for hypertension, her blood pressure decreased from 208/129 mmHg to 150/68 mmHg. Pulsed Doppler echocardiography revealed new paradoxical flow at the mid-ventricle. Decreased LV pressure following treatment with antihypertensive medications may have contributed to the development of early mid-ventricular obstruction and paradoxical flow in the present case. Learning objective: In mid-ventricular obstructive cardiomyopathy, apical aneurysm may be present and cause serious complications such as rupture of the apex and sudden death. In the present case, apical aneurysm newly developed after treatment for hypertension was suggested by advent of paradoxical flow. This case suggests that intraventricular hemodynamic change may become a trigger of paradoxical flow and apical aneurysm, becoming a risk of serious complication.